EFFECTIVE STRATEGY FOR IMPLEMENTING TALENT MANAGEMENT FOR COMPANY IN INDONESIA - Adinda Chairul Ummi; Azhar Aditya; Fenni Annisa Siregar; Risdah Armayana; Sri Mulida; Santa Maria Sibarani (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
A new paradigm in Human Resource Management recently assumes that human resource is an organizational asset (it is known as human capital) that must be managed proactively and strategically. Because the great challenge of management today is to winning a talent war. The talent war is a situation when company competes each other to beat their competitors for the best talent available in the labor market. One of strategies to win this talent war is with talent management; it is implemented to determine, find, develop, and manage and retain a talented employee in an effort to achieve strategic goal and future business needs. This study explains how to apply a talent management strategy as a strategy to develop human resources in public organizations so that it will produce superior human resources in the organization. This study used a qualitative approach with a grounded theory; theoretical studies from the previous studies to create a new research model on the relationship between talent management and the development of superior human resources. The study results found that the importance of aligning talent management strategies with business strategies; this is aimed at developing a talent mindset as well as creating superior human resources today and in the future.